2018
DOI: 10.17305/bjbms.2018.2800
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of long non-coding RNA (lncRNA) expression in hepatitis B patients

Abstract: Long non-coding RNAs (lncRNAs) have been implicated in numerous biological processes, including epigenetic regulation, cell-cycle control, and transcriptional/translational regulation of gene expression. Differential expression of lncRNAs and disruption of the regulatory processes are recognized as critical steps in cancer development. The role of lncRNAs in hepatitis B virus (HBV) infection is not well understood. Here we analyzed the expression of 135 lncRNAs in plasma samples of 82 HBV patients (classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Intriguingly, in a research conducted in Turkey which identified the expression profiles of lncRNAs in patients with hepatitis B, GAS5 was downregulated in CHB, inactive HBsAg carriers, and resolved patients with HBV compared with the healthy control group. However, after 12 months of treatment/follow‐up in all three patient groups, GAS5 significantly increased . The inconsistency here, which might be caused by different HBV virus genotypes or ethnic heterogeneities of the patients, needed to be explored in further studies.…”
Section: Discussionmentioning
confidence: 86%
“…Intriguingly, in a research conducted in Turkey which identified the expression profiles of lncRNAs in patients with hepatitis B, GAS5 was downregulated in CHB, inactive HBsAg carriers, and resolved patients with HBV compared with the healthy control group. However, after 12 months of treatment/follow‐up in all three patient groups, GAS5 significantly increased . The inconsistency here, which might be caused by different HBV virus genotypes or ethnic heterogeneities of the patients, needed to be explored in further studies.…”
Section: Discussionmentioning
confidence: 86%
“…Previously, Yilmaz Susluer et al 18 applied qRT‐PCR to analyze the expression of 135 lncRNAs in plasma from 82 patients with chronic HBV infection (classified as chronic patients, inactive carriers, or resolved patients) and 81 healthy volunteers. Compared with healthy controls, they identified 15 upregulated and 7 downregulated lncRNAs from initial diagnosis to the 12th month of treatment/follow‐up in patients with chronic HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Peng and colleagues have analyzed the lung transcriptome in severe acute respiratory syndrome‐associated coronavirus (SARS‐CoV)‐infected mice and reported that the expression of 504 annotated and 1406 unannotated lncRNAs had significant changes . In addition, other viral families, such as Zika virus, hepatitis B virus (HBV), and hepatitis C virus, have been shown upon host infection to lead to differential expression of host lncRNAs compared with uninfected controls. Therefore, the differential expression of lncRNAs in various cell types following viral infection appears to be a widespread phenomenon and not a property attributable to one viral family or host target cell.…”
Section: Differential Expression Of Lncrnasmentioning
confidence: 99%